Chemical and Biological Aspects of Marine Sponges from the Family Mycalidae - Habener, Leesa J.; Hooper, John N. A.; Carroll, Anthony R. (Planta Medica, 2016)
Sponges are a useful source of bioactive natural products. Members of the family Mycalidae, in particular, have provided a variety of chemical structures including alkaloids, polyketides, terpene endoperoxides, peptides, and lipids. This review highlights the compounds isolated from Mycalid sponges and their associated biological activities. A diverse group of 190 compounds have been reported from over 40 specimens contained in 49 references. Over half of the studies have reported on the biological activities for the compounds isolated. The polyketides, in particular the macrolides, displayed potent cytotoxic activities (< 1 µM), and the alkaloids, in particular the 2,5-disubstituted pyrrole derivatives, were associated with moderate cytotoxic activities (1–20 µM). The pyrrole alkaloids and the cyclic peroxides appear to be phylogenetically restricted to sponges and thus might prove useful when applied to sponge taxonomy. The observed diversity of chemical structures suggests this family makes a good target for targeted biodiscovery projects.
Keywords: Mycale; Mycalidae; sponges; Porifera; bioactivity; alkaloids; polyketides; chemical diversity